Structural and functional microbial diversity of sandy soil under cropland and grassland - Magdalena Frąc; Jerzy Lipiec; Bogusław Usowicz; Karolina Oszust; Małgorzata Brzezińska (PeerJ, 2020)
Background Land use change significantly alters soil organic carbon content and the microbial community. Therefore, in the present study, the effect of changing cropland to grassland on structural and functional soil microbial diversity was evaluated. The specific aims were (i) to identify the most prominent members of the fungal communities and their relevant ecological guild groups; (ii) to assess changes in the diversity of ammonia-oxidizing archaea; (iii) to determine the relationships between microbial diversity and selected physical and chemical properties. Methods We investigated microbial diversity and activity indicators, bulk density and the water-holding capacity of sandy soil under both cropland and 25-year-old grassland (formerly cropland) in Trzebieszów, in the Podlasie Region, Poland. Microbial diversity was assessed by: the relative abundance of ammonia-oxidizing archaea, fungal community composition and functional diversity. Microbial activity was assessed by soil enzyme (dehydrogenase, β-glucosidase) and respiration tests. Results It was shown that compared to cropland, grassland has a higher soil organic carbon content, microbial biomass, basal respiration, rate of enzyme activity, richness and diversity of the microbial community, water holding capacity and the structure of the fungal and ammonia-oxidizing archaea communities was also altered. The implications of these results for soil quality and soil health are also discussed. The results suggest that grassland can have a significant phytosanitary capacity with regard to ecosystem services, due to the prominent presence of beneficial and antagonistic microbes. Moreover, the results also suggest that grassland use may improve the status of soil organic carbon and nitrogen dynamics, thereby increasing the relative abundance of fungi and ammonia-oxidizing archaea.